Mechanistic insights into CLNS1A-mediated chemoresistance and tumor progression in non-small cell lung cancer - Wei, Tong-You Wade; Hsia, Jiun-Yi; Yang, Tsung-Ying; Huang, Yu-Xu; Wang, Guo-Zhi; Liu, Yi-Chung; Wang, Yi-Wun; He, Fangzhou; Chen, Jo-Mei Maureen; Zhao, Guo-Jun; Lyu, Ping-Chiang; Su, Li-Jen; et al. (Cancer letters, 2025)
CLNS1A is a chloride channel protein and an essential component of the methylosome complex, which additionally comprises PRMT5 and MEP50. In this study, we investigated its contribution to lung cancer and its potential as a therapeutic target. Analysis of transcriptomic datasets and western blotting revealed that CLNS1A, PRMT5, and MEP50 were overexpressed in lung cancer tissues, with elevated CLNS1A expression correlating with poor patient survival. CLNS1A overexpression enhanced platinum clearance from cells, increased the IC50 values for chemotherapy, and improved cell survival. Conversely, the knockdown of CLNS1A increased drug accumulation, reduced survival, and increased sensitivity to chemotherapy. The 3W mutant, a chloride channel-defective variant with steric hindrance at key bottleneck residues, impaired chloride ion transport, thereby reducing drug resistance, migration, and anchorage-independent growth. Mechanistically, CLNS1A promotes drug efflux through its chloride channel activity and activates the FAK-SRC-RAC1 pathway to enhance motility and clonogenicity. It also facilitates PRMT5-mediated RUVBL1 methylation to support anti-apoptotic DNA damage response signaling. In vivo, CLNS1A overexpression accelerated tumor growth and reduced survival, whereas CLNS1A knockdown sensitized tumors to cisplatin, enhancing therapeutic efficacy. These findings suggest that CLNS1A is a potential biomarker and therapeutic target, and its inhibition offers a strategy to overcome drug resistance and limit the metastatic progression of lung cancer. •CLNS1A is overexpressed in NSCLC and predicts poor patient survival.•CLNS1A promotes drug efflux and chemoresistance via chloride channel activity.•CLNS1A enhances migration and anchorage-independent growth in lung cancer.•CLNS1A enables DDR via PRMT5-dependent RUVBL1 methylation and survival signaling.•CLNS1A inhibition sensitizes tumors to cisplatin and reduces tumor burden in mice.